Long-term follow up of rates of secondary malignancy and late relapse of two trials using radioimmunotherapy consolidation following induction chemotherapy for previously untreated indolent lymphoma. Issue 10 (3rd October 2015) - Reiss, Jonathan; Link, Brian; Ruan, Jia; Furman, Richard; Coleman, Morton; Leonard, John; Martin, Peter
Abstract : Existing data suggest that myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) peak in incidence 5–10 years following exposure to ionizing radiation, while most publications report less than 5 years of follow-up after radioimmunotherapy (RIT). We report the rate of secondary MDS/AML among 60 patients treated with two front-line sequential chemotherapy-RIT trials with over 11 years of follow-up. Among 35 patients evaluated after fludarabine-RIT and 25 patients evaluated after CVP (cyclophosphamide, vincristine, prednisone)-RIT treatment, the crude, cumulative and Kaplan–Meier rates of MDS/AML at 11 years of follow-up from the combined trials were 0.12/person, 0.010/person-year and 14% (95% confidence interval [CI] 5–24%), respectively. Additionally, we found that patients treated with RIT consolidation appear to have durable remissions but that relapses after 10 years do occur. Studies of efficacy and secondary MDS/AML that report fewer than 10 years of follow-up likely underestimate risk.